Effect of dopamine on early larvae of sea urchins, Mesocentrotus nudus and Strongylocentrotus intermedius. Issue 6 (9th September 2020) - Kalachev, Alexander V.
Abstract: Larvae of many echinoids are known to be phenotypically plastic and capable of changing the growth rate of their post‐oral arms depending on the microalgae concentration in their habitat. As literature data show, developing larvae use chemosensation to detect algae in the environment and "adjust" the rate of growth of their post‐oral arms through dopamine signaling. According to our results, dopamine has a significant effect on the post‐oral arm growth in early larvae of two sea urchin species, Mesocentrotus nudus and Strongylocentrotus intermedius . The dopamine effect depends on concentration: the higher the dopamine concentration in the water, the shorter the post‐oral arms. We suggest that the pattern of response to variation in dopamine concentration, manifested by early larvae of both species, is similar to that observed at different concentrations of microalgae. Abstract : Whisker plots of the data sets for post‐oral arms lengths of 4‐day‐old larvae from different experimental groups of Mesocentrotus nudus (left) and Strongylocentrotus intermedius (right). Black dots are mean values and whiskers are 95% confidence intervals of the means. Highlights: Larvae of Mesocentrotus nudus and Strongylocentrotus intermedius responded to different concentrations of dopamine similar to their response to different concentrations of microalgae. Dopamine can be used to manipulate length of post‐oral arms in early larvae of sea urchins.